2018
DOI: 10.1002/gj.3272
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of tectonic sequences, depositional systems, and tectonic controls of the sedimentary fills of the rift‐related Wenchang Formation in the Lufeng Depression, Pearl River Mouth Basin, China

Abstract: Different sequence types were formed in various stages associated with tectonic variations and changes of the sediment supply in the rift‐related Wenchang Formation. Based on cores, wire logging, and seismic data, the sequence stratigraphy, depositional systems, and controls on the depositional systems of the Wenchang Formation in the Lufeng Depression were studied. The Wenchang Formation developed braided‐delta, lacustrine, fan‐delta, and nearshore subaqueous fan deposits and represents one first‐order sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…According to the characteristics of well logs and seismic reflection of the interfaces within E 2 w, two first-order sequence boundaries (SB1 and SB4) and two second-order sequence boundaries (SSB2 and SSB3) were identified (Figures 2 and 3). Based on the identified sequence boundaries, the rift-related Wenchang Formation can be further divided into one first-order sequence (E 2 w) and three second-order sequences, including SSQ1, SSQ2, and SSQ3, which correspond to the early syn-rift phase (Ew 6 ), rift climax phase (Ew 5 -Ew 4 ), and late syn-rift phase (Ew 3 -Ew 1 ) [36]. SSQ1 is composed of transgressive systems tract (TST) and highstand systems tract (HST).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the characteristics of well logs and seismic reflection of the interfaces within E 2 w, two first-order sequence boundaries (SB1 and SB4) and two second-order sequence boundaries (SSB2 and SSB3) were identified (Figures 2 and 3). Based on the identified sequence boundaries, the rift-related Wenchang Formation can be further divided into one first-order sequence (E 2 w) and three second-order sequences, including SSQ1, SSQ2, and SSQ3, which correspond to the early syn-rift phase (Ew 6 ), rift climax phase (Ew 5 -Ew 4 ), and late syn-rift phase (Ew 3 -Ew 1 ) [36]. SSQ1 is composed of transgressive systems tract (TST) and highstand systems tract (HST).…”
Section: Geological Settingmentioning
confidence: 99%
“…According to the core description, thin-section analysis, shape of logging curve, and seismic reflect patterns, as well as papers published about the study area [3,36], four main sedimentary facies were recognized in the study area: braided-delta facies, lacustrine facies, fan-delta facies, and nearshore subaqueous fan facies (Figures 4-6), which can be further divided into a variety of subfacies and microfacies. Three subfacies developed in braided-delta facies: braideddelta plain, braided-delta front, and predelta facies, and the sandbodies of braided-delta front are the main focus of this study.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The sediment supply is another factor that affects the development of large fans, and even controls their development, which is also concluded in numerous other studies (e.g. Liu et al ., 2017, 2019; Jia et al ., 2019; Gao et al ., 2020; Patruno et al ., 2020). Earlier analyses of the source‐to‐sink system in the study area (Liu et al ., 2019) indicated that the sediment that came from Hainan Island (north of the QB) was probably transported by the Lingshui and Wanquan rivers (see the section Factors controlling clinothem development for details), and that there were consequently two independent source‐to‐sink systems.…”
Section: Significance For Hydrocarbon Explorationmentioning
confidence: 99%